Fractionated dose versus bolus dose of isobaric injection ropivacaine (0.75%) for patients undergoing elective caesarean section under spinal anaesthesia: A randomized, double-blind study - Anita Pareek; Dilip Kochar; Richa Kachhawa; Kritika Bohra; Satyaprakash; Satvik Kachhawa (Journal of Applied Pharmaceutical Research, 2023)
Background: Spinal anaesthesia (SA) using a bolus dose of Ropivacaine (0.75%) is known for its rapid onset but potential chances of hypotension. Administering Ropivacaine (0.75%) in fractions with intervals between the doses, has shown to establish a dense block, prolong analgesia and maintain better hemodynamic stability. This study aimed to compare the efficacy of fractionated and bolus doses of Ropivacaine (0.75%) in patients undergoing elective lower segment caesarean section (LSCS) under spinal anaesthesia. Methods: In a randomized, double-blinded trial, sixty patients scheduled for elective LSCS were enrolled and assigned to two groups. Group A received a single bolus spinal anaesthesia using Ropivacaine (0.75%) (2.5ml), while Group B received a fractionated dose approach: two-thirds of the total Ropivacaine (0.75%) dose (1.6ml) initially, followed by one-third dose (0.9ml) after 90 seconds. Results: The onset of sensory block (Group A: 3.59±1.31 min, Group B: 4.25±0.63 min) and motor block (Group A: 5.49±2.30 min, Group B: 7.34±11.28 min), as well as the duration of analgesia, were significantly longer in Group B (233.33±16.47 min) compared to Group A (185.17±20.61 min) (P < 0.05). Hemodynamic stability was superior in Group B, with all patients showing better stability than those in Group A. Conclusion: Utilizing a fractionated dose of Ropivacaine (0.75%) in spinal anaesthesia results in an extended duration of analgesia and improved hemodynamic stability compared to a bolus dose approach.